Logistic models and algorithms for a biomass transportation system - Pidchaporn Panyoyai (2018)
The purpose of this study is to determine the vehicle routing plan in order to minimize transportation cost for a biomass logistical system. The transportation system in this study consists of one power plant center and potential supply sites. We started with an idea for building the cost function based on the assumption that the total distance traveled can be reduced if some suppliers are left out of the routing. To do this, we created two mathematical models: P1 and P2. P1 is developed by relaxing the traveling salesman problem to minimize the cost of the power plant picking up agricultural waste, and P2 is created to help decide whether the power plant would have to pick up the waste, or whether the suppliers should deliver the waste to the power plant in order to minimize the overall transportation cost in the system. To test whether these models work, we simulated the distance traveled. Simulation results show that the P2 model is suitable for the transportation system where product price is low relative to transportation cost. After testing the simulations, we did a case study on 439 supply sites in Chiang Mai city. The case study results are similar to those obtained from the simulations, indicating that the created model is workable.